Paradigma Baru Pertanggungjawaban Pidana Advokat Terhadap Tindak Pidana Peradilan Menurut UU No. 1 Tahun 2023 - Auliya Bestgati; Maroni M; Maya Shafira; Deni Achmad; Mamanda Syahputra Ginting (Media Hukum Indonesia (MHI), 2026)
The legal profession enjoys immunity in performing defense duties; however, in practice this immunity often conflicts with the offense of contempt of court. This study aims to analyze the new paradigm of criminal liability for advocates following the enactment of Law Number 1 of 2023 on the National Criminal Code (KUHP Nasional) and to examine the limits of professional protection for advocates. The research employs a normative juridical method using statutory and case approaches. The findings indicate that Article 281 of the National Criminal Code provides clearer and more explicit regulation of offenses against judicial proceedings compared to the previous Criminal Code. Although Article 16 of the Advocate Law guarantees legal protection, acts of misbehaving in court committed in bad faith may still give rise to criminal liability. A case study of the Central Jakarta District Court Decision Number 521/Pid.B/2019/PN Jkt.Pst confirms that professional immunity does not apply to conduct that constitutes a pure criminal offense and undermines the dignity of the court. This study concludes that the National Criminal Code clarifies the boundary between legitimate advocacy and contempt of court, requiring advocates to balance client defense with respect for the authority of the judiciary